40-Year CHD Mortality Trends and the Role of Risk Factors in Mortality Decline: The North Karelia Project Experience - Jousilahti, Pekka; Laatikainen, Tiina; Salomaa, Veikko; Pietilä, Arto; Vartiainen, Erkki; Puska, Pekka (Global Heart)
In the 1960s and early 1970s, coronary heart disease (CHD) mortality in Finland was the highest in the world, and within Finland, mortality was particularly high in the eastern part of the country. The North Karelia Project, the first large community-based cardiovascular diseases prevention program was established in 1972 to reduce the extremely high CHD mortality through behavioral change and reduction of the main cardiovascular disease risk factors among the whole population of North Karelia, the easternmost province of Finland. During the 40-year period from 1972 to 2012, smoking prevalence, serum total cholesterol, and systolic blood pressure declined markedly, except a small increase in serum cholesterol levels between 2007 and 2012. From the early 1970s to 2012, CHD mortality decreased by 82% (from 643 to 118 per 100,000) among working-age (35 to 64 years) men. Among working-age women, the decline was 84% (from 114 to 17 per 100,000). During the first 10 years, changes in these 3 target risk factors explained nearly all of the observed mortality reduction. Since the mid-1980s, the observed reduction in mortality has been larger than the predicted reduction. In the early 1970s, premature CHD mortality (35 to 74 years) was about 37% higher among Eastern Finnish men and 23% higher among Eastern Finnish women, compared with men and women in Southwestern Finland. During the last 40 years, premature CHD mortality declined markedly in both areas, but the decline was larger in Eastern Finland and the mortality gap between the two areas nearly disappeared.HighlightRisk factor reduction explains major part of CHD mortality decline in Eastern FinlandKey for prevention is population wide risk factor reduction through lifestyle changesPopulation based prevention is the most cost effective and sustainable way to improve heart health